EFFECTIVE DESIGN FOR TRUST BY CENTERING DISABLED USER EXPERIENCE - Herdegen, Hanna; Wittkower, D.E. (AoIR Selected Papers of Internet Research, 2023)
While conducting multidisciplinary research, spanning engineering, social sciences, and humanities, on Internet of Things device (henceforth, IoT) adoption and use within disability communities, the authors noticed differences in the conceptualization and operationalization of “trust” across practical and disciplinary settings in the context of data privacy and IoT devices. We seek to present a conceptualization of trust which we believe, when pursued earnestly by designers, will be most broadly and universally effective in generating trust among users.In this presentation, following a review of conceptualizations and operationalizations of trust in a data privacy context, we will present a critique and reformulation of “trust” that centers marginalized perspectives, focusing most of all on disabled experience but also seeking to decenter privileged perspectives and keep experiences of BIPOC, LGBTQ+ persons, and women closely in view. Since power is most visible at the margins, centering marginalized perspectives is most likely to find the outlines and structures of power, and design centered on marginalized experiences is likely to be more universal than is a focus on privileged experiences even when supplemented with post hoc and ad hoc accommodations. We conducted this analysis from the frameworks of disability studies, phenomenology and postphenomenology, and feminist ethics of care.